Leadership Trust in Enhancing Career Commitment of Educators at State Madrasah Aliyah in the Riau Archipelago Province - M. Sidik; Ahmad Syukri; Muhammad Fadhil (International Journal of Education, Vocational and Social Science, 2025)
Effectiveness. Leadership Trust in Enhancing Career Commitment of Educators at State Madrasah Aliyah in the Riau Archipelago Province. Dissertation. Islamic Education Management, Postgraduate Program at UIN Sulthan Thaha Saifuddin Jambi, 2025. Educators at Madrasah Aliyah Negeri (MAN) play a crucial role in shaping students' character. However, currently many teachers lack commitment to their careers, which affects the quality of education. This research shows that leadership beliefs play a very important role in enhancing the career commitment of educators. When leaders are able to provide clear direction, motivation, and support, teachers will feel more inspired and engaged in their work. This will have a positive impact on the quality of student learning. Leadership confidence is important because, first, it can foster a positive learning environment: With strong leadership, schools can create a conducive atmosphere for the growth of students and teachers. Second, it increases motivation and work enthusiasm: Inspirational leadership can ignite teachers' spirits to continue learning and developing. Thirdly, improving the quality of education. Committed teachers will give their best to their students. Fourth, making MAN a model of educational excellence. The conclusion from the research findings is that strong leadership is the key to enhancing the career commitment of educators at MAN. Thus, the quality of education at MAN can be improved and the school can become a center of educational excellence. Good leadership can change everything. With strong leadership, teachers will be more motivated, students will receive a better education, and MAN will become a superior school.